A Familial Risk Analysis of Emotional Dysregulation: A Controlled Study. Issue 9 (July 2018) - Biederman, Joseph; Chan, James; Faraone, Stephen V.; Woodworth, K. Yvonne; Spencer, Thomas J.; Wozniak, Janet R.
Objective: Children with deficits in emotional regulation operationalized by scores on the Child Behavior Checklist (CBCL) Attention Problems, Aggressive Behavior, and Anxious-Depressed subscales are more likely than others to manifest adverse outcomes. However, the transmission of this profile has not been well studied. The main aim of this study was to investigate the familiality of this profile.Method: Participants were youth probands with bipolar I (BP-I) disorder ( N = 140), ADHD ( N = 83), and controls ( N = 117) and their siblings. Based on the CBCL emotional dysregulation profile, we classified children with severe emotional dysregulation (aggregate cut-off score ≥210) and emotional dysregulation (aggregate cut-off score ≥ 180 and <210).Results: Emotional dysregulation profile scores correlated positively between probands and siblings.Conclusion: Youth with emotional dysregulation are at increased risk to have siblings with similar deficits, suggesting that emotional dysregulation runs in families.